Preliminary Study of Ge-DLC Nanocomposite Biomaterials Prepared by Laser Codeposition - Jelinek, Miroslav; Kocourek, Tomáš; Jurek, Karel; Jelinek, Michal; Smolková, Barbora; Uzhytchak, Mariia; Lunov, Oleg (Nanomaterials (Basel, Switzerland), 2019)
This paper deals with the synthesis and study of the properties of germanium-doped diamond-like carbon (DLC) films. For deposition of doped DLC films, hybrid laser technology was used. Using two deposition lasers, it was possible to arrange the dopant concentrations by varying the laser repetition rate. Doped films of Ge concentrations from 0 at.% to 12 at.% were prepared on Si (100) and fused silica (FS) substrates at room temperature. Film properties, such as growth rate, roughness, scanning electron microscopy (SEM) morphology, wavelength dependent X-ray spectroscopy (WDS) composition, VIS-near infrared (IR) transmittance, and biological properties (cytotoxicity, effects on cellular morphology, and ability to produce reactive oxygen species (ROS)) were studied in relation to codeposition conditions and dopant concentrations. The analysis showed that Ge-DLC films exhibit cytotoxicity for higher Ge doping.
Keywords: doped biomaterials; DLC; pulsed laser deposition; germanium; cytotoxicity; apoptosis; reactive oxygen species